Attentional Strategies During Rowing - D. Longman,; J.C. Hutchinson,; J.T. Stock,; J.C.K. Wells, (Journal of Basic & Applied Sciences, 2014)
This investigation explored the relationship between task intensity, competitive setting, and attentional strategy in collegiate rowers. Here, the associative-dissociative dimension of attentional focus is considered. Associative thoughts are task-related, whereas dissociative thoughts are not. Previous work has linked associative strategies with higher level performance, and higher intensities of exercise (i.e. those which exceed the ventilatory threshold). Male and female collegiate rowers (N = 298) completed three training sessions (one each at low, moderate, and high intensity) and two races (short and long distance). Results revealed that the higher the training intensity, the greater the degree of association. A greater degree of association was also observed in competition as opposed to training, and in short distance versus long distance races. There was no gender difference in attentional strategy. Finally, it was shown that the variation in attentional strategy was inversely proportional to exercise intensity. These findings support previous work examining the effect of task intensity on attentional focus [1], in a field based setting. Furthermore, new insight is offered regarding how competition interacts with intensity in this relationship.